A Physically Based Model for Preferential Water Flow and Solute Transport in Drained Agricultural Fields. Issue 3 (22nd March 2021) - Holbak, M.; Abrahamsen, P.; Hansen, S.; Diamantopoulos, E.
Abstract: Preferential water flow and associated solute transport in agricultural soils may influence the quality of groundwater and surface waters like streams and lakes. This is due to the rapid transport of agrochemicals, immediately after application, through subsurface drainpipes and surface water. Multiple field experiments attribute this to the occurrence of continuously connected pathways, called here biopores, connecting the soil surface directly with the drainpipes. We developed a physically based model describing preferential flow and transport in biopores directly connecting the upper soil layers with the drainpipes or deeper layers of the soil matrix. Based on field investigations, biopores with specific characteristics can be parameterized as classes with different vertical and horizontal distributions. Water flow and solute transport in biopores are described with a simple mass balance approach assuming instantaneous movement. The model was tested against experimental data from a column experiment with an artificial biopore and showed good results in simulating biopore flow initiation dynamics. However, further field and laboratory experiments are needed to validate the model across the soil profile. We illustrate the performance of the new approach, by conducting five theoretical simulations assuming a two‐dimensional simulation domain with different biopore parametrizations, from none to several different classes. The simulation results agreed with experimental observations reported in the literature, indicating rapid transport from the soil to the drainpipes. Furthermore, the different biopore parametrizations resulted in distinctly different leaching patterns, raising the expectation that biopore properties could be estimated or constrained based on observed leaching data and direct measurements. Plain Language Summary: This is optional but will help expand the reach of your paper. Information on writing a good plain language summary is available here. Key Points: A new model for describing fast transport of solutes to tile drains Biopore parameters may be constrained by smoke or tracer experiments The new model represents correctly experimental observation on the initiation and termination of biopore flow